MASTER CLASS AS THE FORM OF PROFESSIONAL TRAINING OF THE FUTURE STEM-TEACHER OF PRIMARY SCHOOL - Андрієвська, B. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article describes the specifics of organization and conduct of the master class as a form of professional training of the future STEM teacher of primary school. The following types of master classes are provided: "STEM project preparation and implementation", "STEM lesson preparation and implementation", "Preparation and organization of the maker space". Attention is paid to the study of the components of the master classes, respectively, the form of work with students: information, demonstration, practical, final. The information component of the master class involves getting acquainted with the peculiarities of the organization and implementation of the STEM project, the STEM lesson and the maker space at various educational stages. The demonstration component involves familiarizing students with specific examples of the STEM project, the STEM lesson, the maker space, and the tactics of their deployment. The practical component involves the students performing their own task - developing a STEM project, STEM lesson, and a maker space from a topic proposed by the instructor; acquaint students with the specifics of the theme selection for the STEM project, the STEM lesson, the maker space, the substantiation of the topic, and the definition of its promise. The final component involves familiarizing students with a methodology for evaluating the results of independent work, analyzing the results, discussing, expressing their thoughts on improving the results. Stages of master classes are specified. The separate stages of master classes are considered: organization of the educational STEM-space in the classroom; an example of the STEAM project "The symbol of life - Bread" is presented and a series of problem issues of the project is highlighted; the means of ICT support for the future STEM elementary school teacher are considered.